Governing excess: Boxing, biopolitics and the body - Hardes, Jennifer Jane (Theoretical criminology, 2020)
During the late 18th to late 19th centuries, practices of duelling and prize fighting were criminalized in Britain, while boxing remained legal. Through a genealogical method, this article locates discourses, primarily law, medicine, policing and science, to trace these mechanisms of criminalization and legalization. Focusing on the jurisdictions of the United Kingdom and the United States, I argue that the legalization of boxing did not simply emerge as a part of a ‘civilizing process’. Rather, I explain these processes of criminalization and legalization in the context of biopolitical rationalities of governance. In contrast to its contemporaries, boxing was rationalized as a scientific ‘sport’ that fitted with wider biopolitical visions of public health and well-being: allegedly it did not breed violence or threaten the public peace but was instead practised by skilled technicians. However, the biopolitical management of human life within rational and scientific form comes at a price: life’s ontological need for expression, and the drive to experience and witness boxing’s corporeal excesses remains a ghostly presence threatening to undo the sweet ‘science’.